Phylogeny of Protopolybia Ducke, 1905 and taxonomic revision of the Protopolybia exigua species-group (Hymenoptera: Vespidae, Polistinae), with description of four new species - Junior, José N. A. Dos Santos; Silveira, Orlando T.; Carpenter, James M. (Zootaxa, 2015)
A first phylogenetic hypothesis is proposed for Protopolybia Ducke, 1905 based on cladistic analysis of 31 species. New evidence in support of monophyly of the genus is presented. A revision of the Protopolybia exigua species-group is also presented. Protopolybia diligens (Smith, 1857), stat. resurr. is revalidated. Four new species are described: P. collombiana Santos, Silveira & Carpenter, sp. nov., P. clypeata Santos, Silveira & Carpenter, sp. nov., P. similis Santos, Silveira & Carpenter, sp. nov., and P. potiguara Santos, Silveira & Carpenter, sp. nov. Protopolybia holoxantha (Ducke, 1904) and P. rubrithorax Bequaert, 1944 are redescribed. New synonymy is proposed for P. bituberculata Silveira & Carpenter, 1995 =Polybia nana Cameron, 1912 (nom. praeocc., nec de Saussure 1863), syn. nov. New records and description of the male genitalia are provided for some of the species of the P. exigua species-group.